My brilliant friend - Ferrante, Elena; Goldstein, Ann, 1949- (New York : Europa Editions, 2012)
Beginning in the 1950s Elena and Lila grow up in Naples, Italy, mirroring two different aspects of their nation.
Prologue : eliminating all the traces -- Childhood : the story of Don Achille -- Adolescence : the story of the shoes.
Translation of: L'amica geniale.
"Book one: childhood, adolescence."
Keywords: Friendship -- Fiction; Naples (Italy) -- Fiction